A Review Article on Nutraceuticals – An Impact on Conventional Health Care - Mohd. Wasiullah; Piyush Yadav; Vinay Kumar Deepak; Shruti Soni (International Journal of Nutritions, 2025)
Nutraceuticals, combining nutrition and pharmaceuticals, have transformed healthcare. This review explores their classification, scope, benefits, and challenges. Nutraceuticals, including dietary supplements, functional foods, herbal products, and fortified foods, promote health and prevent diseases. The global market, valued at $117 billion, is expanding rapidly, fueled by the growing focus on health. Key benefits are boosted health benefits, fewer side effects, natural options improved nutrition. Classification is traditional (conventional) nutraceuticals (e.g., lycopene, omega-3 fatty acids) and non-traditional nutraceuticals (e.g., fortified foods, recombinant nutraceuticals). Health applications are cancer management, cardiovascular diseases, Alzheimer’s disease, Parkinson’s disease, obesity, diabetes, and kidney diseases. It also includes challenges like, shelf-life management, managing growth of SKUs, traceability and serialization, and storage space optimization. There are various innovations in nutraceuticals, such as functional ingredients and formulations, personalized nutrition solutions, advanced delivery systems, plant-based and sustainable ingredients, blockchain technology and supply chain transparency, etc. Nutraceuticals offer a promising approach to healthcare, with a growing market and innovative solutions.
Keywords: Health Benefits; functional food; market growth; nutraceuticals